HUBUNGAN FEAR OF MISSING OUT (FOMO) DENGAN SELF-ESTEEM PADA SISWA SMP DI ERA DIGITAL: SEBUAH KAJIAN KEPUSTAKAAN EKSTENSIF - Muhammad Zulfahmiansyah (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
The persistent engagement of junior high school (SMP) students with social media platforms in the era of digital hyperconnectivity has given rise to a psychological phenomenon known as Fear of Missing Out (FoMO) an existential anxiety stemming from the subjective perception that others are having more meaningful experiences. This study aims to investigate the dynamics of the relationship between FoMO and self-esteem among junior high school students through a library research approach. Analysis was conducted by synthesizing empirical and theoretical findings from more than ten national and ten reputable international journals using a comparative thematic analysis framework. The synthesis reveals a global consensus on a significant negative correlation between self-esteem and FoMO: adolescents with low self-esteem consistently exhibit higher levels of FoMO as compensation for social validation deficits. This study further identifies a paradoxical anomaly in which high social self-esteem can intensify aggressive digital existence-seeking behavior, and uncovers a mediator–moderator architecture encompassing upward social comparison, self-control, self-compassion, and parental technoference. These findings affirm that mitigating the destructive impact of FoMO demands an orchestrated intervention of psychoeducation, digital literacy strengthening, and redefinition of parenting warmth rather than mere technological restriction. ABSTRAK Keterlibatan remaja Sekolah Menengah Pertama (SMP) yang konstan terhadap platform media sosial di era hiperkonektivitas digital telah melahirkan fenomena psikologis yang dikenal sebagai Fear of Missing Out (FoMO), yakni kecemasan eksistensial akibat persepsi subjektif bahwa orang lain memiliki pengalaman yang lebih bermakna. Penelitian ini bertujuan menginvestigasi dinamika hubungan antara FoMO dan self-esteem pada siswa SMP melalui pendekatan kajian kepustakaan (library research). Analisis dilakukan dengan menyintesis temuan empiris dan teoritis dari lebih dari sepuluh jurnal nasional dan sepuluh jurnal internasional bereputasi menggunakan kerangka analisis tematik komparatif. Hasil sintesis membuktikan adanya konsensus global mengenai korelasi negatif yang signifikan antara self-esteem dan FoMO: remaja dengan harga diri rendah secara konsisten menunjukkan tingkat FoMO yang lebih tinggi sebagai kompensasi atas defisit validasi sosial. Penelitian ini juga mengidentifikasi anomali paradoksikal di mana self-esteem sosial tinggi justru memantik kebutuhan eksistensi digital yang agresif, serta mengungkap arsitektur variabel mediator dan moderator yang meliputi upward social comparison, kontrol diri, self-compassion, dan parental technoference. Temuan ini menegaskan bahwa mitigasi dampak destruktif FoMO menuntut orkestrasi intervensi psikoedukasi, penguatan literasi digital, dan redefinisi kehangatan pola asuh bukan sekadar restriksi teknologi.